Water exploitation index, plus (WEI+), (2000-2022) ... - Zal, Nihat; Staron, Marek; Sdi@Eea.Europa.Eu (European Environment Agency, 2025)
An indicator comparing water use versus renewable freshwater resources as percentage in a given area and time resolution e.g. annual water scarcity at country level. ...